2022
DOI: 10.3390/sym14030578
|View full text |Cite
|
Sign up to set email alerts
|

ZL-Completions for ZL-Semigroups

Abstract: In this paper, we generalize a common completion pattern of ordered semigroups to the fuzzy setting. Based on a standard L-completion ZL, we introduce the notion of a ZL-semigroup as a generalization of an L-ordered semigroup, where L is a complete residuated lattice. For this asymmetric mathematical structure, we define a ZL-completion of it to be a complete residuated L-ordered semigroup together with a join-dense L-ordered semigroup embedding satisfying the universal property. We prove that: (1) For every c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Rv2477c is a ribosome accessory factor, also known as EttA, which is an ATPase that enhances translation efficiency. It has also recently been shown to bind the ribosome near the P-site (peptidyl transfer center), potentially interfering with binding of aminoglycosides [56], and loss-of-function mutations observed in drug-resistant clinical isolates of M. tuberculosis have shown to confer resistance to STR [13]. The ranking of both genes using the CRISPRi-DR model are within the top 12 enriched genes in STR.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Rv2477c is a ribosome accessory factor, also known as EttA, which is an ATPase that enhances translation efficiency. It has also recently been shown to bind the ribosome near the P-site (peptidyl transfer center), potentially interfering with binding of aminoglycosides [56], and loss-of-function mutations observed in drug-resistant clinical isolates of M. tuberculosis have shown to confer resistance to STR [13]. The ranking of both genes using the CRISPRi-DR model are within the top 12 enriched genes in STR.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…That slowdown is exacerbated by plateauing of China‐made exports to mature markets in the rich, industrialized West. China now seeks to transform its growth pattern from the past export‐oriented one that heavily relies on foreign market (or the so‐called “international circulation”) to a new, more balanced pattern of “dual circulation,” in which the “internal circulation” (of domestic market) is expected to play a mainstay role, complemented and supported by the “international circulation” (Yu, 2020). While making efforts to sell domestically, the Chinese industries are seeking new markets abroad beyond the industrialized West for their products so as to better utilize the huge production capacity built over years.…”
Section: Potential Match Between Supply and Demand Is The Foremost Ne...mentioning
confidence: 99%
“…Nimbhorkar et al [31] suggested a fuzzy weakly 2-absorbing ideal of a lattice. Some notable recent developments in fuzzy set theory can be found, for example, in artificial intelligence [32], supply chain [33], symmetry [34], computational intelligence [35], and some of them use fuzzy set theory in algebraic systems with different applications such as civil engineering [36][37][38][39], etc., where both symmetry and asymmetry have occurred.…”
Section: Introductionmentioning
confidence: 99%